Myocardial Damage, Inflammation, Coagulation, and Platelet Activity During Catheter Ablation Using Radiofrequency and Pulsed-Field Energy - Osmancik, Pavel; Bacova, Barbora; Hozman, Marek; Pistkova, Jitka; Kunstatova, Veronika; Sochorova, Veronika; Waldauf, Petr; Hassouna, Sabri; Karch, Jakub; Vesela, Jana; Poviser, Lukas; Znojilova, Lucie; et al. (JACC. Clinical electrophysiology, 2024)
BACKGROUND: Pulsed-field ablation (PFA) represents a new, nonthermal ablation energy for the ablation of atrial fibrillation (AF). Ablation energies producing thermal injury are associated with an inflammatory response, platelet activation, and coagulation activation. OBJECTIVES: This study aimed to compare the systemic response in patients undergoing pulmonary vein isolation (PVI) using pulsed-field and radiofrequency (RF) energy. METHODS: Patients with AF indicated for PVI were enrolled and randomly assigned to undergo PVI using RF (CARTO Smart Touch, Biosense Webster) or pulsed-field (Farapulse, Boston-Scientific) energy. Markers of myocardial damage (troponin I), inflammation (interleukin-6), coagulation (D-dimers, fibrin monomers, von Willebrand antigen and factor activity), and platelet activation (P-selectin, activated GpIIb/IIIa antigen) were measured before the procedure (T1), after trans-septal puncture (T2), after completing the ablation in the left atrium (T3), and 1 day after the procedure (T4). RESULTS: A total of 65 patients were enrolled in the pulsed-field ablation (n = 33) and RF ablation (n = 32) groups. Both groups were similar in baseline characteristics (age 60.5 ± 12.7 years vs 64.0 ± 10.7 years; paroxysmal AF: 60.6% vs 62.5% patients). Procedural and left atrial dwelling times were substantially shorter in the PFA group (55:09 ± 11:57 min vs 151:19 ± 41:25 min; P < 0.001; 36:00 ± 8:05 min vs 115:58 ± 36:49 min; P < 0.001). Peak troponin release was substantially higher in the PFA group (10,102 ng/L [IQR: 8,272-14,207 ng/L] vs 1,006 ng/L [IQR: 603-1,433ng/L]). Both procedures were associated with similar extents (>50%) of platelet and coagulation activation. The proinflammatory response 24 h after the procedure was slightly but nonsignificantly higher in the RF group. CONCLUSIONS: Despite 10 times more myocardial damage, pulsed-field ablation was associated with a similar degree of platelet/coagulation activation, and slightly lower inflammatory response. (The Effect of Pulsed-Field and Radiofrequency Ablation on Platelet, Coagulation and Inflammation; NCT05603637).
Keywords: venae pulmonales; Treatment Outcome; lidé středního věku; Catheter Ablation; platelet; pulsed-field ablation; Humans; Middle Aged; senioři; katetrizační ablace; apoptosis; Aged; coagulation; Inflammation; Pulmonary Veins; zánět; fibrilace síní; radiofrequency ablation; lidé; Atrial Fibrillation; inflammation; atrial fibrillation; výsledek terapie